2004
DOI: 10.2174/1389557043487321
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib (STI571) Resistance in Chronic Myelogenous Leukemia: Molecular Basis of the Underlying Mechanisms and Potential Strategies for Treatment

Abstract: Following the paradigm set by STI571, protein tyrosine kinase inhibitors are emerging as a promising class of drugs, capable of modulating intracellular signaling and demonstrating therapeutic potential for the treatment of proliferative diseases. Although the majority of chronic phase CML patients treated with STI571 respond, some patients, especially those with more advanced disease, relapse. This article reviews the reasons for relapse and, in particular, analyses resistance resulting from Bcr-Abl tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 0 publications
0
108
0
1
Order By: Relevance
“…7 These clones are selected by continuous exposure to ABL kinase inhibitors. 4,8 With the exception of the 'gatekeeper' mutation, T315I, the most clinically relevant mutations confer resistance against the first-generation ABL kinase inhibitor, imatinib, but can still be targeted using one of the second-generation ABL kinase inhibitors, dasatinib or nilotinib. 7 Tetramerization of ABL through the N-terminal coiled-coil region (CC) of BCR is essential for aberrant ABL-kinase activation.…”
Section: Introductionmentioning
confidence: 99%
“…7 These clones are selected by continuous exposure to ABL kinase inhibitors. 4,8 With the exception of the 'gatekeeper' mutation, T315I, the most clinically relevant mutations confer resistance against the first-generation ABL kinase inhibitor, imatinib, but can still be targeted using one of the second-generation ABL kinase inhibitors, dasatinib or nilotinib. 7 Tetramerization of ABL through the N-terminal coiled-coil region (CC) of BCR is essential for aberrant ABL-kinase activation.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, crystallographic studies have revealed an improved topological fit for the ABL protein. 20 This is due to the design of more potent compounds that incorporate alternative binding groups.…”
Section: Pharmacologymentioning
confidence: 99%
“…Point mutations that reduce imatinib binding through a direct mechanism are generally positioned around the imatinib binding site, and diminish imatinib binding through alterations in amino acid side chains or topographical changes that sterically hinder the binding of imatinib. Phe317 and Thr315 are examples of this type of BCR-ABL point mutation (Cowan-Jacob et al, 2004). Point mutations that reduce imatinib binding through an indirect mechanism utilize the distinct binding mode of a drug to BCR-ABL.…”
Section: Bcr-abl Point Mutations As a Mechanism Of Imatinib Resistancementioning
confidence: 99%